2019
DOI: 10.1073/pnas.1908762116
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in thyroid hormone receptor α1 cause premature neurogenesis and progenitor cell depletion in human cortical development

Abstract: SignificanceThyroid hormone deficiencies are the most common preventable causes of intellectual disability. We report that mutations in the thyroid hormone receptor α1 gene (THRA) that result in intellectual disability also reduce brain size. Using human THRA mutation stem cell models, we studied the impact of THRA mutations on human brain development by combining quantitative lineage analysis, gene expression analyses, and novel assays of neuroepithelium formation. We found that THRA regulates the balance bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…To date, about 20 missense and frameshift mutations of THRA have been described [121,[136][137][138][139][140]. Clinical features of patients include many symptoms commonly present in hypothyroidism, such as bradycardia, constipation, skeletal dysplasia (macrocephaly, late fontanelle closure, and epiphyseal dysgenesis), delayed bone growth and psychomotor development, and intellectual disability [72,121,141]. In other words, the pathological signs involve those tissue that normally rely on TRα.…”
Section: Th Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…To date, about 20 missense and frameshift mutations of THRA have been described [121,[136][137][138][139][140]. Clinical features of patients include many symptoms commonly present in hypothyroidism, such as bradycardia, constipation, skeletal dysplasia (macrocephaly, late fontanelle closure, and epiphyseal dysgenesis), delayed bone growth and psychomotor development, and intellectual disability [72,121,141]. In other words, the pathological signs involve those tissue that normally rely on TRα.…”
Section: Th Resistancementioning
confidence: 99%
“…Moreover, a de novo missense mutation (R384C) in TRα1 was found in a patient affected by an autism spectrum disorder [143]. Recently, it has been reported that TRα1 is required for normal neural progenitor cell proliferation in human cerebral cortical development; as a consequence, mutations in the TRA gene cause a reduction of brain size and intellectual disability [141].…”
Section: Th Resistancementioning
confidence: 99%
“…Two intriguing studies using novel models of thyroid hormone receptor alpha ( THRA ) mutations, which cause thyroid hormone resistance syndrome (RTH), were published in 2020. Krieger et al [ 1 ] demonstrated the essential actions of thyroid hormone receptor alpha (TRα) on the normal development of the human cerebral cortex. The authors previously reported that adult patients with RTH had intellectual impairments, especially affecting nonverbal IQ and delayed sensorimotor processing [ 2 ].…”
Section: New Understandings Of Thyroid Hormone Actions and Signaling mentioning
confidence: 99%
“…Indeed, these findings were consistent with those of a mouse model with a mutant variant of TRα1, which showed a range of central nervous system abnormalities [ 3 ], but the cellular mechanisms of the impacts of THRA (the gene encoding TRα) on neural development remained unclear. Krieger et al [ 1 ], using THRA mutant patient-derived induced pluripotent stem cell (iPS) models in combination with a quantitative lineage analysis, gene expression analysis, and novel assays of neuro-epithelium formation, showed that THRA regulates the balance between progenitor self-renewal and neurogenesis, thereby affecting the overall brain mass and especially the cortex. A structural modeling study of the ligand-binding domain of TRα1 demonstrated that the THRA mutation facilitates corepressor binding.…”
Section: New Understandings Of Thyroid Hormone Actions and Signaling mentioning
confidence: 99%
“…Thyroid hormone is a key endocrine signal conserved in all vertebrates, including humans, regulating many homeostatic processes such as growth, reproduction and energy metabolism. TH also regulates CNS development ( Gothié et al, 2017 ) by influencing all neurodevelopmental processes, including cell cycle progression, fate choice, migration, differentiation, axo- and synaptogenesis, and myelination ( Zoeller and Rovet, 2004 ; Moog et al, 2017 ; Krieger et al, 2019 ; Vancamp et al, 2020 ). Under pathophysiological conditions, TH acts on each of these processes, promoting regeneration in the adult fish brain that retained large numbers of NSCs ( Grandel et al, 2006 ; Bhumika and Darras, 2014 ).…”
Section: The Potential Of Thyroid Hormone As a Pro-repair Cuementioning
confidence: 99%